PROMOTING STUDENTS' CRITICAL THINKING SKILLS THROUGH DIGITAL STORYTELLING - Cepri Maulana, - (2022)
Pandemic has changed the way students learn and requires teacher to integrate technology and digital media into online classroom. Digital Storytelling has been considered as one of the alternative strategies to promote critical thinking skills for secondary school students. Therefore, this study aims to investigate how Digital Storytelling is implemented to help promote students' critical thinking skills. A qualitative case study was employed involving one teacher and one class of ninth-grade students in a public junior high school in West Bandung Regency. Data were collected through three main instruments, namely classroom observation, interview with the teacher, and document analysis covering the lesson plan and students' reflective assignment. The collected data were analyzed and interpreted based on five-step-models of critical thinking promotion proposed by Duron, Limbach, & Waugh (2006) as well as the Digital Storytelling Elements. The Digital Storytelling was presented by employing Power Point Presentation. The teacher fully optimized her voice to deliver the whole story and gave freedom for the teacher to pause the story whenever needed. The findings of this study reveal that the teacher employed 6 out of 7 elements of Digital Storytelling in her lessons. In promoting the students' critical thinking skills, the teacher utilized a pattern throughout the study, that is, read-pause-reread the story in the online classroom. She frequently provided a sufficient access for students to express their ideas during the breaks between pages of the story. For instance, the teacher posted many questions to encourage students to share their ideas and think critically by giving explanation and analysis in the arguments during the learning process. The critical thinking promoted in the form of students' answer towards questions as well as respond to another respond stated by their classmates. In addition, she delivered the story in a normal pace with frequent breaks, allowing the students to have a chance in active involvement. These breaks offered opportunity for the students to promote their critical thinking skills especially their analysis and explanation skills. Keywords: Digital Storytelling, online classroom, critical thinking skills